Design of an Arts Community Center with a Neo-Vernacular Architectural Approach in Padang Lawas - Novrial, Novrial; Siregar , M. Azharuddin Salim (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
In general, North Sumatra is a province with a variety of arts, such as fine arts, dance, and various types of traditional music. Among them, Padang Lawas Regency is one of the regencies in North Sumatra with cultural heritage in the land of Dalihan Natolu. Various art activities are always held, where art is part of the life process and a symbol of the identity of the people of Padang Lawas Regency. Until now, various cultural activities continue to be maintained, preserved and introduced. The preservation and development of arts in Padang Lawas is quite good, as evidenced by the existence of art groups that continue to grow and develop in the community, as well as several art activities whose intensity of implementation is increased by the government as a form of preservation and introduction of Padang Lawas culture. The development of this art is not matched by the provision of supporting facilities. For this reason, an art community center building is needed to accommodate art activities in Padang Lawas. The theme to be applied is Neo-Vernacular Architecture. In addition, a permanent place is needed to exhibit works of art, history and culture so that domestic and foreign tourists can enjoy and visit at any time without waiting for special events. By planning an Art Community Center in Padang Lawas Regency, apart from being a place for the community to learn, perform, maintain and develop art over time, it is also one aspect of attracting tourists to visit Padang Lawas Regency.